Leadership in non-profit organisations - PARSEHYAN, BESTE GÖKÇE (My University, 2017)
Emerging at the end of the twentieth century, non-profit sector has taken on a new significance. Non-governmental organisations, health institutions, educational institutions and museums are examples for the variety of non-profit organisations. Museums are defined as the symbols of national cultures and bridges uniting the past with the present. However, it may be suggested that this definition has lost its validity on a large scale due to globalism that penetrated into our lives in the twentieth century. Globalism and multiculturalism played an important role in the industrialisation of culture, and being the symbols of culture, museums assumed the form of dynamics within this industry. Accordingly, the concept of museum leadership gained importance. The increasing competition amongst museums makes leadership more crucial. Compared to other sectors, museums have not been studied enough in terms of leadership and the late, but the necessary attempt to improve museum leadership is of vital importance for cultural industry. This study first discusses leadership and non-profit organisations separately, and afterwards, it investigates into leadership in non-profit organisations. Lastly, it elaborates on museum leadership, which is a popular concept of the modern day.
Keywords: Leadership; Non-Profit Organisations; Third Sector; Museums; Museum Leadership; Liderlik; Kâr Amacı Gütmeyen Kuruluşlar; Üçüncü Sektör; Müzeler; Müze Liderliği